Ag–ZnO heterostructure nanoparticles with plasmon-enhanced catalytic degradation for Congo red under visible light1. Issue 43 (14th May 2015) - Liu, Xu; Li, Weibo; Chen, Nan; Xing, Xinxin; Dong, Chengjun; Wang, Yude
<x xml:space="preserve">Abstract</x> Ag–ZnO heterostructured nanoparticles by a one-step solvothermal route exhibit outstanding photocatalytic efficiency for Congo red in aqueous solution under visible light irradiation.